Розробка та експериментальне дослідження приладу для вимірювання щільності ґрунту по ширині захвату прикочуючого котка просапної сівалки - Артеменко, Д. Ю.; Настоящий, В. А.; Філімоніхін, Г. Б.; Artemenko, Dmitry; Nastoyaschyuy, Vladislav; Filimonihin, Genadiy (КНТУ, 2015)
В статті розглянуто проблему вимірювання щільності ґрунту по ширині захвату прикочуючого котка просапної сівалки. Проаналізовані відомі методи і знаряддя для визначення щільності ґрунту, з’ясовані їх недоліки та запропоновано нову конструкцію приладу. Проведено експериментальне дослідження нового приладу та отримані результати його роботи, які показали високу ефективність його використання. Working out and experimental research of the device for measurement of soil density on width of capture of a condensing skating rink of a seeder is the purpose of the given work. In article the problem of measurement of soil density on width of capture of a condensing skating rink of a seeder is considered. Known methods and adaptations for definition of soil density are analysed, their lacks are revealed and the new design of the device is offered. Experimental researches of the new device are spent in vitro. Results of consolidation of soil under a skating rink of a curvilinear profile are received. As a result of the spent work it has been defined that the section design and the square form of a cutting element of the device, and also its longitudinal orientation gives the chance to make measurements of soil density with split-hair accuracy. Also the obtained data can be used for working out of new designs of condensing skating rinks.
Working out and experimental research of the device for measurement of soil density on width of capture of a condensing skating rink of a seeder
Keywords: щільність ґрунту; прилад для вимірювання щільності ґрунту; прикочуючий коток сівалки; soil density; the device for measurement of density of the soil; condensing skating rink of a seeder